CURRENT ISSUES OF THE SYSTEMATIZATION OF SOCIAL LEGISLATION OF UKRAINE - Dyban, Maksym (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
Objective: to analyze the legal features of the concept of "systematization of legislation"; carry out a study of certain types of systematization of the social legislation of Ukraine; to single out proposals for improving the process of systematization of legislation in the field of social protection of the population in Ukraine. Research methods: general scientific and special methods were used during scientific research. In particular, the definition of concepts: "systematization of social legislation", "codification of social legislation" was formulated using the logical-semantic method. The comparative legal method was used during the analysis of the common and distinctive features of the forms of systematization of social legislation, the characteristics of the ratio of trends in the further development of the systematization of social legislation and directions for the improvement of systematization. During the generalization of the classification of tasks and functions of the systematization of social legislation, classification, grouping, system-structural and system-functional methods were applied. With the help of special legal and statistical methods, the theoretical and practical problems of the systematization of social legislation have been established. In turn, the structural-logical method was used to determine the possibilities of eliminating the outlined problems and optimizing the systematization of social legislation in Ukraine. Results: it was analyzed that the sphere of social protection of the population in Ukraine needs systematization of the current social legislation taking into account the main trends of the European Community. Discussion: the problem of the ineffectiveness of the social legislation of Ukraine regarding the provision of proper social protection of the population and the realization of constitutional rights and guarantees by a person in the specified sphere of legal relations was raised.